Endoscopic Surveillance in Idiopathic Achalasia - (:unkn) unknown (CUREUS INC, 2021)
Idiopathic achalasia is a rare esophageal dysmotility disorder of unknown etiology with only palliative treatment available. Many studies have established a significantly increased risk of esophageal cancer in patients with achalasia. However, current guidelines advise against routine surveillance due to low absolute risk and a paucity of high-quality evidence and cost-effectiveness assessments. This review aims to assess the need for routine endoscopic surveillance in achalasia based on a growing body of literature calling in support of it, mainly due to the increased risk of esophageal cancer. We searched PubMed and Google Scholar electronic databases for articles within the last 10 years using the keywords 'achalasia', 'cancer,' 'neoplasms

'screening

and 'surveillance.' After excluding pseudoachalasia/secondary achalasia, other esophageal dysmotility disorders, and associations with malignancies outside the esophagus, we selected 31 articles for this review. Through these articles, we identified areas of focus for ongoing and future research that may result in significant risk reduction of complications, including esophageal cancer and beyond.
Keywords: achalasia; cancer; esophageal squamous cell carcinoma; esophageal adenocarcinoma; screening; surveillance; esophageal dysmotility; ESOPHAGEAL CANCER; GENERAL-POPULATION; BARRETTS-ESOPHAGUS; MANAGEMENT; RISK; ADENOCARCINOMA; CARCINOMA; DIAGNOSIS; SYMPTOMS